Graph-Based Learning: A Paradigm Shift in Financial Analytics - Sandeep Kadiyala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Graph-based learning represents a paradigm shift in financial analytics by leveraging the inherently interconnected nature of financial ecosystems to extract deeper insights and enable more effective decision-making. This article models financial data as networks of entities connected by meaningful relationships, preserving crucial structural information that traditional tabular and time-series methods often fail to capture. Graph-based learning has demonstrated transformative potential across the financial industry landscape, from detecting sophisticated fraud schemes to optimizing investment portfolios, enhancing risk assessment, personalizing customer experiences, and analyzing cryptocurrency networks. By explicitly representing and analyzing relationships between financial entities—whether customers, transactions, or assets—graph neural networks and related techniques uncover hidden patterns, reveal market structures, and predict behaviors that remain invisible to conventional analytical approaches. The growing adoption of these technologies across major financial institutions reflects their proven ability to generate tangible business value by improving predictive accuracy, reducing risk exposure, enhancing customer relationships, and providing competitive insights in an increasingly complex and interconnected global financial system.
Keywords: Graph Neural Networks; Fraud Detection; Portfolio Optimization; Risk Assessment; Customer Analytics; Cryptocurrency Analysis